The Thermal and Settlement Characteristics of Crushed-Rock Structure Embankments of the Qinghai-Tibet Railway in Permafrost Regions Under Climate Warming - Mei, Qihang; Yang, Bin; Chen, Ji; Zhao, Jingyi; Hou, Xin; Liu, Youqian; Wang, Jinchang; Zhang, Shouhong; Dang, Haiming (Frontiers in Earth Science, 2021)
The temperature difference at the top and bottom of the crushed-rock layer can drive the heat convection inside. Based on this mechanism, crushed-rock revetment structure and U-shaped crushed-rock structure formed by the combination of crushed-rock revetment and base are widely used in the construction and maintenance of the Qinghai-Tibet Railway as cooling measures in permafrost regions. To explore the stability of different forms of crushed-rock structure embankments under climate warming, the temperature and deformation data of a U-shaped crushed-rock embankment (UCRE) and a crushed-rock revetment embankment (CRRE) are analysed. The variations in temperature indicate that permafrost beneath the natural sites and embankments is degrading but at different rates. The influence of embankment construction and the cooling effect of the crushed-rock structure make permafrost degradation beneath the embankments slower than that beneath the natural sites in the shallow layer and faster than that beneath the natural sites in the deep layer. Moreover, the convection occurring in the crushed-rock base layer during the cold season makes the degradation of permafrost beneath the UCRE slower than that in the CRRE. The faster degradation of permafrost causes the accumulated deformation of the CRRE to be far greater than that of the UCRE, which may exceed the allowable value of the design code. The analysis shows that the stability of the UCRE meets the engineering requirements and the CRRE needs to be strengthened in warm and ice-rich permafrost regions under climate warming.